Cation speciation, compactness, and structure‐property correlations in manganese aluminosilicate glasses. Issue 12 (19th July 2022) - So, Byoungjin; Ding, Yicong; Limbach, René; Pyo, Jae‐Young; de Macedo, Guilherme N. B. M.; Li, Kai; Friebe, Christian; Otto, Felix; Schaal, Maximilian; Liu, Chao; Heo, Jong; Wondraczek, Lothar
Abstract: We report on the elastic properties of x MnO‐Al2 O3 ‐(6‐ x )SiO2 manganese aluminosilicate glasses, in which pronounced exchange coupling and antiferromagnetic interaction occurs among the paramagnetic Mn 2+ ions. X‐ray absorption reveals a Mn‐O bond length of ∼2.1 Å, and a distance of ∼3 Å between Mn 2+ ions in sixfold coordination, further corroborated by electron paramagnetic resonance and dynamic photoluminescence spectroscopy. This indicates the presence of edge‐sharing MnO6 units, in resemblance to edge‐sharing MnO8 in the crystalline Spessartine garnet Mn3 Al2 [SiO4 ]3 . We argue that these cluster species have a profound effect on material stiffness: the compact structure of manganese aluminosilicate glasses enables a Young's modulus in the 100 GPa range and a Poisson's ratio of about 0.3. This exceeds the compositional trend with cation field strength observed for other aluminosilicate glasses.